2021
DOI: 10.18870/hlrc.v11i2.1244
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Faculty Members’ Perceptions and Experiences of Classroom Assessment: A Case Study of a Public University in Afghanistan

Abstract: Objective: The primary goal of the study was to examine students’ perceptions of classroom assessment at a public university in Afghanistan. Exploring current assessment practices focused on student and faculty members lived experiences was a secondary goal. The study also sought to collect evidence on whether or not the new assessment policy was effective in student achievement. Method: Authors used an explanatory sequential mixed-methods design to conduct the study. Initially, we applied the Students Percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…In this process, the student will initially picture the whole activity at a glance, outline the principles involved, and gather and arrange relevant materials required before putting up the demonstration just to ensure that the activity incorporates all necessary principles and assumptions. This confirmed what Herrera et al., [23] said that PBA tasks assess all aspects of student learning by determining means by which students assimilate information, store, and apply information in novel ways. However, Nitko argued that every learning target cannot be assessed using PBA.…”
Section: Performance-based Assessmentsupporting
confidence: 83%
“…In this process, the student will initially picture the whole activity at a glance, outline the principles involved, and gather and arrange relevant materials required before putting up the demonstration just to ensure that the activity incorporates all necessary principles and assumptions. This confirmed what Herrera et al., [23] said that PBA tasks assess all aspects of student learning by determining means by which students assimilate information, store, and apply information in novel ways. However, Nitko argued that every learning target cannot be assessed using PBA.…”
Section: Performance-based Assessmentsupporting
confidence: 83%
“…Besides, according to Boud and Dawson (2021), Gebremariam and Gedamu (2022), Hailay (2017), andTeshome (2016) in the educational system in Ethiopia teachers' assessment for learning practices seems too questionable. From the assessment for learning practice expected to ensure the students' learning improvement through day to day classroom practice (Bordoh et al, 2015;Popham, 2017;Mussawy et al, 2021;Yan and Pastore, 2022). This implies that assessment is used as a means of learning progress for improvement (Molloy et al, 2020;Hussain et al, 2021).…”
Section: Assessment For Learning Practicementioning
confidence: 99%
“…In the instructional process effective assessment for learning practice results the sustainable students' learning improvement. This assessment for learning practice has its own objective, to assist students' learning progress in improving their learning, updating their cognitive process of learning and develop the abilities through assessment for learning concepts and practices (Teshome, 2016;Mussawy et al, 2021). Previous studies (e.g., Popham, 2008Popham, , 2017Black and Wiliam, 2009;Pattalitan, 2016;Farrel, 2017;Sultana, 2019;Gedamu and Shewangezaw, 2020;Schildkamba et al, 2020) have confirmed that this type of assessment is an ongoing process of learning and teaching to safeguard that educational objectives and specific goals of subject matters are met, respectively.…”
Section: Assessment For Learning and Learning Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' perceptions in this study refer to how students perceive the assessment (Mussawy, 2009) in the aspects of task, test, teacher's observation, feedback, and redesign when LORA is implemented in the reading class as the framework developed from Jones and Saville's (2016) model. They are observed using five-Likert scale questionnaire and semi-structured interview (Alokozaya, 2022& Phongsirikul, 2018.…”
Section: )mentioning
confidence: 99%